Diabetic patients with acute coronary syndromes in contemporary European registries: characteristics and outcomes - Lettino, Maddalena; Andell, Pontus; Zeymer, Uwe; Widimsky, Petr; Danchin, Nicolas; Bardaji, Alfredo; Barrabes, Jose A; Cequier, Angel; Claeys, Marc J; De Luca, Leonardo; Dörler, Jakob; Erlinge, David; et al. (European heart journal. Cardiovascular pharmacotherapy, 2017)
Aims: Among patients with acute coronary syndromes (ACS), those with diabetes mellitus (DM) are at particularly high risk of recurrent cardiovascular events and premature death. We aimed to provide a descriptive overview of unadjusted analyses of patient characteristics, ACS management, and outcomes up to 1 year after hospital admission for an ACS/index-ACS event, in patients with DM in contemporary registries in Europe. Methods and results: A total of 10 registries provided data in a systematic manner on ACS patients with DM (total n =28 899), and without DM (total n= 97 505). In the DM population, the proportion of patients with ST-Segment Elevation Myocardial Infarction (STEMI) ranged from 22.1% to 64.6% (other patients had non-ST-Segment Elevation Myocardial Infarction (NSTEMI-ACS) or unstable angina). All-cause mortality in the registries ranged from 1.4% to 9.4% in-hospital; 2.8% to 7.9% at 30 days post-discharge; 5.1% to 10.7% at 180 days post-discharge; and 3.3% to 10.5% at 1 year post-discharge. Major bleeding events were reported in up to 3.8% of patients while in hospital (8 registries); up to 1.3% at 30 days (data from two registries only), and 2.0% at 1 year (one registry only). Registries differed substantially in terms of study setting, site, patient selection, definition and schedule of endpoints, and use of various P2Y12 inhibitors. In most, but not all, registries, event rates in DM patients were higher than in patients without DM. Pooled risk ratios comparing cohorts with DM vs. no DM were in-hospital significantly higher in DM for all-cause death (1.66; 95% CI 1.42-1.94), for cardiovascular death (2.33; 1.78 - 3.03), and for major bleeding (1.35; 1.21-1.52). Conclusion: These registry data from real-life clinical practice confirm a high risk for recurrent events among DM patients with ACS, with great variation across the different registries.
Keywords: infarkt myokardu bez ST elevací; nestabilní angina pectoris; Hemorrhage; Risk Assessment; lidé; Middle Aged; Prognosis; Percutaneous Coronary Intervention; prognóza; Recurrence; infarkt myokardu s elevacemi ST úseků; registrace; Risk Factors; Female; krvácení; Evropa; ST Elevation Myocardial Infarction; hodnocení rizik; diabetes mellitus 1. typu; inhibitory agregace trombocytů; Platelet Aggregation Inhibitors; lékařská praxe - způsoby provádění; Humans; Angina, Unstable; recidiva; Diabetes Mellitus, Type 1; koronární angioplastika; Registries; Hospital Mortality; Non-ST Elevated Myocardial Infarction; Practice Patterns, Physicians'; lidé středního věku; diabetes mellitus 2. typu; mužské pohlaví; koronární bypass; Diabetes Mellitus, Type 2; Coronary Artery Bypass; Time Factors; ženské pohlaví; Acute Coronary Syndrome; časové faktory; akutní koronární syndrom; Aged; Male; Europe; mortalita v nemocnicích; rizikové faktory; senioři